Moral Foundations and Obesity: The Role of Binding vs. Individualizing Foundations in Shaping Weight Stigma - Cristian Catena-Fernández; Alejandro Magallares (International Review of Social Psychology)
Weight stigma significantly affects the quality of life for individuals with obesity in Western societies. While previous research has used moral foundations theory to predict attitudes toward stigmatized groups, such as the poor, immigrants, and sexual minorities, its application to weight-related stigma remains underexplored. This research explores the relationship between moral foundations, the moralization of obesity, and weight stigma in an underrepresented European context. In a pre-registered correlational study (Study 1), we found that binding and individualizing foundations differentially predicted the moralization of obesity and weight stigma. A follow-up pre-registered experiment (Study 2) suggested that highlighting the societal benefits of purity, a binding moral foundation, over care, an individualizing moral foundation, may increase the moralization of obesity and heighten weight stigma. These findings contribute to deepening understanding of the moral roots of weight stigma and underscore the importance of considering moral values in efforts to mitigate it.